Circuit element modeling scheme for a hairpin resonator by using EDA tool - Hock G.C.; Devkumar S.; Badjian M.H.; Chakrabarty C.K. (2023)
This paper describes how a circuit element modeling scheme was used to analyze and optimize a microstrip open loop resonator. With the discrete optimization, realistic values can be assigned to the designed resonator. The circuit element models of the open loop resonator represent the structure very well with respect to electromagnetic models. Besides that, it provides a fine computation speed of simulation to study the resonator. The understanding and intuition of particular segment of the structure is very helpful and valuable for the designers to make the initial estimation. 2008 IEEE.